MRNet: A Software-Based Multicast/Reduction Network for Scalable Tools - Roth, Philip; Arnold, Dorian; Miller, Barton P. (University of Wisconsin-Madison Department of Computer Sciences, 2003)
We present MRNet, a software-based multicast/reduction network for building scalable performance and system administration tools. MRNet supports multiple simultaneous, asynchronous collective communication operations. MRNet is flexible, allowing tool builders to tailor its process network topology to suit their tool?s requirements and the underlying system?s capabilities. MRNet is extensible, allowing tool builders to incorporate custom data reductions to augment its collection of built-in reductions. We evaluated MRNet in a simple test tool and also integrated into an existing, real-world performance tool with up to 512 tool back-ends. In the realworld tool, we used MRNet not only for multicast and simple data reductions but also with custom histogram and clock skew detection reductions. In our experiments, the MRNet-based tools showed significantly better performance than the tools without MRNet for average message latency and throughput, overall tool start-up latency, and performance data processing throughput.